Pengembangan Ekonomi Syariah Melalui Lembaga Keuangan Berdasarkan Pandangan Prof. Imam Suprayogo - Shafwan Tsauri (ITB AAS INDONESIA Surakarta, 2023)
Sharia economics is an economic system that refers to Islamic teachings and rules that refer to the Koran and Hadith. The point of view taken from this economic perspective refers to countries where the majority of the population is Muslim, whose development can then lead to progress in the development of Islamic society at the time of the Prophet Muhammad. Prof. Imam Suprayogo has a well-known concept of thought, namely the concept of education based on the Qur'an, with the view of Tarbiyah Ulul Albab. The implementation is a combination of the form of Islamic boarding schools and tertiary institutions which are known to be Islamic education based on dhikr. Described with a metaphor as a tree of knowledge that is solid because it is supported by strong roots and rods. So according to this view, tree trunks are described as knowledge whose sources are from the Qur'an and also Hadith. As for strong roots, it is described as the ability to speak language which then leads to this view as the basis for studying deeper knowledge and foundations in international relations.